Comparative Analysis of Anthocyanin Compositions and Starch Physiochemical Properties of Purple-Fleshed Sweetpotato “Xuzishu8” in Desert Regions of China - Yan, Hui; Zhang, Yungang; Ahmad, Muhammad Qadir; Liu, Yaju; Kou, Meng; Ma, Meng; Li, Chen; Arisha, Mohamed Hamed; Tang, Wei; Wang, Xin; Gao, Runfei; Song, Weihan; et al. (Frontiers in Plant Science, 2022)
The present study was undertaken to determine the scope of sweetpotato cultivation in arid regions of China. For this purpose, we investigated yield, anthocyanin compositions and physiochemical properties of starch in purple-fleshed sweet potato (PFSP) ‘Xuzishu8’ under humid (zi8-X) and arid (zi8-D) environments of China. The experiment was conducted in three replications in both environments during 2019 and 2020. The yield and anthocyanidins contents of PFSP were significantly higher in the arid conditions as compared to humid. Zi8-X and zi8-D both revealed the presence of three anthocyanidins, namely, cyanidin (Cy), peonidin (Pn), and pelargonidin (Pg). Cy and Pn accounted for 36.40% and 63.54% of the total anthocyanidins in zi8-X, while in zi8-D, they were found as 26.13% and 73.80%, respectively. Quantitaive analysis of these anthocyanins was performed using HPLC-DAD/ESI-MS/MS which revealed eighteen anthocyanins including nine Cy, eight Pn and one Pg. Out of which, eleven anthocyanins showed a significant difference under both conditions. Starch and amylopectin contents were found to be increased by 15.39% and 4.71%, respectively, while the amylose concentration was reduced by 15.54% under the arid environment. The diameter of the starch granule and the peak viscosity were significantly higher under arid as compared to humid conditions. On the basis of results of this study it seems quite practicable to develop PFSP cultivation in desert regions.